Hume's naturalism - Mounce, H. O. (Routledge, 1999)
Hume's Naturalism provides a clear and concise guide to the debates over whether Hume's empiricism or his 'naturalism' in the tradition of the Scottish 'Common Sense' school of philosophy gained his upper hand. This debate is central to any understanding of Hume's thought. H.O. Mounce presents a beautifully clear guide to Hume's most important works, The Treatise on Human Nature and Dialogues Concerning Natural Religion. Accessible to anyone coming to Hume for the first time, Hume's Naturalism affords a much needed overview of the key concepts of empiricism.